Antioxidant Properties of 2-Hydroxyethyl Methacrylate-Based Copolymers with Incorporated Sterically Hindered Amine - Poláková, L; Raus, V; Kostka, L; Braunová, A; Pilař, J; Lobaz, V; Pánek, J; Sedláková, Z (Biomacromolecules, 2015)
A series of model linear copolymers of 2-hydroxyethyl methacrylate (HEMA) and a sterically hindered amine derivative [N-(2,2,6,6-tetramethyl-piperidin-4-yl)methacrylamide (HAS)] were synthesized and characterized. Scavenging activities of the copolymers against reactive oxygen species (peroxyl and hydroxyl radicals) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals were determined. It was found that copolymers with medium HAS content (3.5-4.0 mol %) were better scavengers than copolymers with lower and higher HAS content and also than polyHEMA and polyHAS homopolymers and the HAS monomer. Importantly, these copolymers compared favorably even to established low-molecular weight antioxidant standards (BHA and dexpanthenol). Monomer reactivity ratios were determined, and the microstructure of the copolymers was assessed. Subsequently, cross-linked copolymers in the powder and film forms with optimal HAS content were synthesized. Their scavenging activities against the three types of radicals were determined, revealing that these hydrogels are potent scavengers of reactive oxygen species.
Keywords: Reactive Oxygen Species; methakryláty; Methacrylates; reaktivní formy kyslíku; Free Radical Scavengers; scavengery volných radikálů